2019
DOI: 10.1017/s1463423619000744
|View full text |Cite
|
Sign up to set email alerts
|

Implementing dementia risk reduction in primary care: a preliminary conceptual model based on a scoping review of practitioners’ views

Abstract: Primary care practitioners (PCPs) do not routinely promote dementia risk reduction. The purpose of this study was to map the published literature on the views of PCPs about dementia risk reduction, in order to identify implementation constructs and strategies crucial to the development of an implementation intervention to support dementia risk reduction in primary care. We undertook a scoping review of the PCPs’ views about promoting brain health for reducing dementia risk. We searched MEDLINE, PsycINFO, CINAH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
6

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 39 publications
0
26
0
6
Order By: Relevance
“…On the other hand, we found several determinants associated with implementation success such as Relative Priority, Available Resources, Leadership engagement, and Culture that Martinez et al [56] did not identify. Relative priority is an implementation barrier identi ed in other PHC studies on cognitive health promotion, which found that professionals relegate health promotion activities to a secondary position and prioritise health problems considered more urgent and important for the patient [57][58][59]. Available resources is a commonly perceived barrier by PHC professionals to the integration of health promotion activities into daily practice [11,56].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, we found several determinants associated with implementation success such as Relative Priority, Available Resources, Leadership engagement, and Culture that Martinez et al [56] did not identify. Relative priority is an implementation barrier identi ed in other PHC studies on cognitive health promotion, which found that professionals relegate health promotion activities to a secondary position and prioritise health problems considered more urgent and important for the patient [57][58][59]. Available resources is a commonly perceived barrier by PHC professionals to the integration of health promotion activities into daily practice [11,56].…”
Section: Discussionmentioning
confidence: 99%
“…Many resources have been, or are currently in the process of being developed (e.g., 11 ). However, previous research has highlighted that there are difficulties faced with implementing effective educational resources and facilitating practice change in primary care 12, 13 . Travers and colleagues conducted a review of educational and behavioural interventions for risk reduction in primary care and suggested that these approaches are at most, moderately effective 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Die Prävention und Strategien der Risiko-Reduktion bei Demenzen [1] geraten zunehmend mehr in das Blickfeld der Versorgungsforschung [2][3][4][5][6]. So haben in einer aktuellen Übersichtsarbeit Escher und Jessen auf die besondere Bedeutung der kardiovaskulären Prävention kognitiver Störungen hingewiesen [7].…”
Section: Hintergrundunclassified
“…Es ist bekannt, dass Patienten gegenwärtig zunehmend an Demenzprävention interessiert sind [11]. Auch HÄ scheinen bereit zu sein, sich in der Demenzprävention zu engagieren [6], obwohl frühere Erhebungen Gegenteiliges berichteten [12]. So wurden von Hausärzten Bedenken geäußert, ob Demenzprävention überhaupt nützlich sei [13].…”
Section: Hintergrundunclassified
See 1 more Smart Citation